'Part of the project of that book was not to be authentic': neo-historical authenticity and its anachronisms in contemporary historical fiction. Issue 2 (3rd April 2017) - Harris, Katharine
Abstract: A redefinition of 'authenticity' is occurring in historical fiction, with the emergence of a 'neo-historical' aesthetic. Wider cultural discourses around authenticity are particularly unstable as evidenced by the renegotiation of the term through social media movements such as Instagram's #liveauthentic community. The neo-historical impulse in fiction participates in these debates. Whereas in much historical fiction criticism the term 'authentic' has been synonymous with 'accurate' – witness the quotation from Sarah Waters in my title – the neo-historical aesthetic is differently authentic. This is evident in the use of conspicuous anachronisms through which the neo-historical both resists and incorporates postmodern discourses about the unreliability of 'factual' historical narratives, proposing instead new kinds of fictional histories, which are authentic in their self-awareness and honest acknowledgement of their inevitable limitations. With reference to #liveauthentic, this paper will explore the neo-historical aesthetic in novels by Emma Donoghue and Sarah Waters and historical fiction criticism from Diana Wallace and Marie-Luise Kohlke. Underpinning these debates are semiotic theories by Jonathan Culler about authenticity and tourism which illuminate the conditions of 'authenticity' and clarify ongoing shifts in its meaning. Rather than deconstructing all history neo-historical aesthetics use the politics and practices of deconstruction and shift the semiotic markers of authenticity to create new, fictionalised 'neo-histories'.